Postoperative results of ventilation tube insertion: a retrospective multicenter study for suggestion of grading system of otitis media with effusion - Chan Il Song; Byung Chul Kang; Chol Ho Shin; Yun Suk An; Tae Su Kim; Hyun Woo Lim; Hyun Joon Shim; Myung Hoon Yoo; Joong Ho Ahn (BMC, 2021)
Abstract Background In otitis media with effusion (OME), it is important to know when to surgically intervene and when careful monitoring is more appropriate. This study aimed to visualize and classify the clinical manifestations of OME and the correlation between the new grading system and postoperative results after ventilation tube insertion (VTI). Methods We classified the collective 1,012 ears from 506 patients into six groups: grade 0 (no effusion), grade I (scant effusion, but abnormal), grade II (effusion less than half of the tympanic cavity), grade III (effusion over half of the tympanic cavity, with air bubbles), grade IV (complete effusion), and grade V (retracted tympanic membrane or hemotympanum without air bubbles). Results The mean age at VTI was 5.2 (±2.9) years and mean duration between diagnosis and operation was 4.1 (±1.8) months. Between the grades, the nature of the middle ear effusion was also significantly different (p < 0.001). The duration of ventilation tube retention after VTI was significantly different when compared between two groups: grade I-IV and grade V (p = 0.019). Our results showed that the recurrence rate, as well as rate of revision VTI, increased as the grade increased (p < 0.001). Conclusions The new grading system of OME using endoscopic otoscope evaluation had a significant correlation with the age at VTI, the nature of middle ear effusion, the recurrence rate of OME, and the rate of revision VTI.